Relationship between Clinicopathological Profile and Tumor Budding Status in Colorectal Adenocarcinoma at Dr. Cipto Mangunkusumo General National Hospital: A Retrospective Study - Dhuhani, Ika; Handjari, Diah Rini; Rahadiani, Nur; Krisnuhoni, Ening; Stephanie, Marini (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2022)
Background: Colorectal adenocarcinoma (CA) is one of the most common malignancies. Tumor budding (TB) status is associated with poor prognosis in patients. Prognosis is influenced by the clinicopathological profile. This study aims to determine the relationship between the clinicopathological profile with TB status in CA at Dr. Cipto Mangunkusumo General National Hospital.Method: A cross-sectional retrospective analytic study using secondary data in the form of cases in large bowel malignancy resection preparations at the Department of Anatomical Pathology in 2019-2021. A total of 213 samples were taken from all cases according to the inclusion and exclusion criteria. Chi square statistical analysis was performed to see the clinicopathological relationship with TB status.Results: Most common TB status were low grade with 92 cases. Most cases were ≥ 50 years old (64.3%), male (50.7%), located in the left colon (77.5%), histopathological degree low grade (85.9%), depth of invasion on pT3 (61.5%), lymphovascular invasion (LVI) (50.2%), lymph node metastasis (52.6%), stage 3 American Joint Committee on Cancer (AJCC (42.3%), without perineural invasion (PNI) (79.3%) and without distant metastases (82.6%). Statistical analysis test showed that there was a significant relationship between the degree of histopathology, depth of invasion, LVI, lymph node metastasis, and AJCC stage (p 0.001) and tumor location (p = 0.036).Conclusion: TB status was significantly related histopathological degree, LVI, lymph node metastasis, depth of invasion, AJCC stage, and tumor location. TB status was not associated with PNI and distant organ metastases.